Resource abundance: Blessing or curse? Comparative analyses of point and diffuse resources - Gildas Dohba Dinga; Ndam Mama; Elvis D. Achuo (Heliyon, 2024)
The objective of this study is to assess the short and long run effects of renewable and non-renewable resource rents on economic growth in Cameroon. Taking crude oil rents and forest resource rents as proxies for non-renewable and renewable resources respectively for the period 1977–2018, we employed the autoregressive and dynamic autoregressive distributive lag (ARDL/DynARDL) modelling frameworks to achieve the stated objective. Results from the ARDL model indicate that, in the short run, both the renewable and non-renewable resources have a positive and significant effect on economic growth but the point resource is more significant than the diffused. A clear disparity in results is however noticed in the long run. While the point resources show that natural resources are a curse to long run growth, the diffuse resources reveal that natural resources are a blessing to long run growth. From the DynARDL simulation, a negative shock of the point resources leads to a fall in economic growth whereas diffuse resource indicates an increase. This shows that point resources are more prone to the resource-curse thesis and diffuse resources to resource-bless thesis. Contingent on these findings, the Cameroon government should ensure a proper allocation of natural resource revenues especially point resource rents to growth-inducing investment or social overhead capital such as open new markets, transport infrastructures, and power sectors, so as to enhance growth and development.